Students’ perceptions of teacher feedback in EFL English class and their self-regulated learning after receiving feedback - Nanin Verina Widya Putri; Ahmad Munir; Syafi’ul Anam (Journal on English as a Foreign Language, 2021)
Teacher feedback is useful information for EFL students’ improvement. It assists students to know their weaknesses and strengths in English learning. However, students might perceive teacher feedback differently from the teacher's intentions. This study examined students’ perceptions of their teacher feedback in English class and investigated their self-regulated learning after receiving feedback. It is a descriptive-qualitative study involving ten EFL students of the senior high school using semi-structured interview questions through online communication. Subsequently, the data were transcribed and analyzed qualitatively using thematic analysis of students’ perceptions of teacher feedback and their self-regulated learning. The finding showed that the students perceived teacher feedback as positive and negative. Upon receiving teacher feedback, the students developed their self-regulated learning, such as setting goals, monitoring, self-motivating, seeking-help, adopting, and self-evaluating in English learning. This study offers implications for English teachers and educators to improve their feedback quality in English classroom assessment.